Pelvic Hydatidosis Mimicking a Malignant Multicystic Ovarian Tumor - Sing, Prem (The Korean Society for Parasitology, 2010)
Echinococcosis is a multisystem disease and has propensity to involve any organ, an unusual anatomical site, and can mimic any disease process. Primary peritoneal echinococcosis is known to occur secondary to hepatic involvement but occasional cases of primary peritoneal hydatid disease including pelvic involvement have also been reported. We report here 1 such case of primary pelvic hydatidosis mimicking a malignant multicystic ovarian tumor where there was no evidence of involvement of the liver or spleen. Our patient, a 27-year-old female, was detected to have a large right cystic adnexal mass on per vaginal examination which was confirmed by ultrasonography. Her biochemical parameters were normal and CA-125 levels, though mildly raised, were below the cut off point. She underwent surgery and on exploratory laparotomy, another cystic mass was found attached to the mesentery of the small gut. The resected cysts were processed histopathologically. On cut sections both large cysts revealed numerous daughter cysts. Microscopic examination of fluid from the cysts revealed free scolices with hooklets and the cyst wall had a typical laminated membrane with inner germinal layer containing degenerated protoplasmic mass. The diagnosis of pelvic hydatid disease was confirmed and patient was managed accordingly. Hydatid disease must be considered while making the differential diagnosis of pelvic cystic masses, especially in endemic areas.